2012
DOI: 10.3389/fimmu.2012.00302
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Human B Cell Phenotypic Profiling

Abstract: To advance our understanding and treatment of disease, research immunologists have been called-upon to place more centralized emphasis on impactful human studies. Such endeavors will inevitably require large-scale study execution and data management regulation (“Big Biology”), necessitating standardized and reliable metrics of immune status and function. A well-known example setting this large-scale effort in-motion is identifying correlations between eventual disease outcome and T lymphocyte phenotype in larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
273
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(289 citation statements)
references
References 178 publications
(313 reference statements)
14
273
2
Order By: Relevance
“…The subset of NSM B-cells has been implicated in immune responses against T-cell independent antigens, however recent studies confirmed their role as a long-lasting memory to T-cell dependent antigens involved in reconstitution of switched memory pool upon antigen restimulation [10]. Changes in NSM fraction were accompanied by increased percentage of immature/ /early-transitional B-cells and activated SM cells, both [8,16,23]. Nevertheless, systemic accumulation of B-cells with CD27+CD21 low phenotype, e.g.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The subset of NSM B-cells has been implicated in immune responses against T-cell independent antigens, however recent studies confirmed their role as a long-lasting memory to T-cell dependent antigens involved in reconstitution of switched memory pool upon antigen restimulation [10]. Changes in NSM fraction were accompanied by increased percentage of immature/ /early-transitional B-cells and activated SM cells, both [8,16,23]. Nevertheless, systemic accumulation of B-cells with CD27+CD21 low phenotype, e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Samples were fixed with FACS lysing solution (BD Biosciences), washed and analyzed in FACS Canto II flow cytometer (BD Biosciences). Based on differential expression of surface markers the following B-cell subsets were identified: immature/ /early-transitional (I/T, CD27-IgD+CD21 low ), late-transitional/naïve (CD27-IgD+CD21+), non-switched memory (NSM, CD27+IgD+), resting class-switched memory (SM, CD27+IgD-CD21+), activated SM (CD27+IgD-CD21 low ), and double-negative (CD27-IgD-) exhausted memory (ExM) as summarized in Figure 1C [8,16,23,25]. Using T-cell panel we identified four subsets within CD4+ or CD8+ gate: naïve (CD45RA+CD45RO-CCR7+), central memory (T CM , CD45RA-CD45RO+CCR7+), effector memory (T EM , CD45RA-CD45RO+CCR7-), and effector memory CD45RA+ (T EMRA , CD45RA+CD45RO-CCR7-) [26,27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further distinction of B cell subsets within CD27 + and CD27 2 cells may help to further define the relevance of these changes. For example, memory CD27 + B cells can be separated into IgD 2 isotypeswitched and IgD + NSM subsets, and CD27 2 B cells can be separated into IgD + mature naive and IgD 2 SwM-like B cells (107). The importance of distinguishing the latter CD27 2 IgD 2 DN B cells that we and others have shown to be elevated in SLE patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In particular IgD, CD27, CD24 and CD38, other than other molecules, may be used to study peripheral B cells in humans. Nevertheless "core" subsets may be identified by using IgD and CD27 expression on CD19 B cells and this kind of classification has been suggested to be useful as potential biomarkers in some autoimmune diseases (Kaminski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%